PENGGUNAAN KAIDAH RASM MANUSKRIP MUSHAF QUR`AN MASJID ASASI PADANG PANJANG (QS. AN-NISA`: 24-147) - Syamsi, Nur; Rosli, Muhammad; Aqilah, Siti; Aisyah, Siti (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
AbstractManuscripts are cultural and historical heritage that contain handwriting, such as Javanese script, Pegan, etc. In Indonesia there are various ancient manuscripts, one of which is the Al-Qur'an mushaf. In accordance with the ijtihad of the ulama, the manuscripts of the Al-Qur'an were written in the Ottoman pattern. Rasm refers to the writing of the Al-Qur'an which is done in a special way, both in writing the pronunciations and in the shapes of the letters used. Meanwhile, the Ottoman rasm is a written, mushaf of the Al-Quran attributed to the caliph Uthman bin Affan which aims to equalize the reading and writing of the Al-Qur'an. However, some Al-Qur'an manuscripts do not use the Ottoman script as a writing guide, such as the Al-Qur'an manuscript stored in the Asasi Padang Panjang mosque. Therefore, it is important to carry out research on rasm, because many people think that the writing of the Al-Qur'an is impossible to bear because its authenticity is guaranteed, and as a form of cultural preservation because manuscripts are part of the cultural and historical heritage of mankind. This research aims to identify the rasm aspects contained in the Al-Qur'an manuscripts of the Asasi Padang Panjang mosque, then compare them with the Indonesian printed Al-Qur'an. The research results show that the use of rasm in this manuscript is inconsistent and uses two different rasm, namely Ottoman and Imla`i. The method used in this research is a qualitative method with a library research model.